Metode Pembelajaran Kolaboratif dalam Meningkatkan Keterampilan Menulis Bahasa Arab - Durrotunnasihah; Putra Ramadani (Global Action and Education for Society, 2024)
This article discusses the application of collaborative learning methods in improving Arabic writing skills. Through a collaborative approach, students are expected to be more active and interactive in the learning process, so that their writing skills can be significantly improved. The study uses a case study method with a qualitative approach involving 30 eleventh-grade students at a madrasah in Jakarta. The learning process lasted 8 weeks, during which time students engaged in a variety of collaborative activities such as group discussions, joint writing, and group projects. Data is collected through observations, interviews, and student writing analysis before and after the application of collaborative methods. Research results showed significant improvements in students' writing skills, in terms of cohesion and coherence, more diverse vocabulary usage, and better sentence structure. These findings show that collaborative learning methods are effective in improving students' Arabic writing skills and are highly recommended for application in Arabic language learning in schools. Further research could explore the application of this method in other language skills such as reading and speaking.